Peran Inklusi Keuangan dalam Mengatasi Ketimpangan Pendapatan di Indonesia - Febriaty, Hastina; Rahayu, Sri Endang; Nasution, Eri Yanti (Fakultas Ekonomi Universitas Samudra, 2022)
The aim of this study is to analyze the role of financial inclusion in the digital economy era and produce financial inclusion strategies and policies in overcoming income inequality in Indonesia. The secondary data used is in the form of time series data from the TW;1:2005 to TW;4:2019 period. The data is sourced from BPS, BI and OJK, then analyzed using the 2SLS technique. The results in the first equation show that financial inclusion variables such as the number of credit accounts, the number of savings accounts (TPF) and the number of MSME loans have no significant effect on economic growth; while the number of ATM machines has a significant effect on PE, and GR has no significant effect on PE. In the second equation, financial inclusion variables such as DPK have a significant effect on GR, JKB have no significant effect on GR, and PE has a significant effect on GR.